Work Stress Analysis of Employees at PT Manusia Alam Indonesia - Viola Taruli Manna Parhusip; Marsofiyati; Ervina Maulida (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Every company needs Human Resources to achieve the company's goals. Therefore, every company must pay attention to its employees by providing a comfortable and fair work environment to all employees. This study aims to analyze the factors that cause work stress in employees of PT. Manusia Alam Indonesia and the methods used to overcome work stress.This research method uses descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. The informants consisted of several employees of PT. Manusia Alam Indonesia who are selected purposively based on employee experience related to work stress. Accompanied by data analysis, starting from data collection, data presentation, and drawing conclusions.From the results of the study, it can be seen that the factors that cause work stress at PT. Manusia Alam Indonesia include, high work demands, tight deadlines, and a less conducive work environment. High work demands often make employees feel overwhelmed with excessive workloads, tight deadlines force employees to work quickly and often reduce employee rest time which has an impact on physical and mental fatigue, a less conducive work environment such as lack of support facilities and unsupportive colleagues are the cause of stress. And to overcome work stress is carried out individually and organizationally. Individual approaches that employees take include, walking, exercising, watching concerts, regulating breathing, seeking fresh air, eating, accessing social media, and taking adequate breaks. Meanwhile, the company's organizational approach to employees includes, vacations and joint sports, health insurance, and a clear evaluation and division of duties.